Mechanisms underpinning AMP-activated protein kinase-related effects on behavior and hippocampal neurogenesis in an animal model of depression. (15th May 2019) - Odaira, Takayo; Nakagawasai, Osamu; Takahashi, Kohei; Nemoto, Wataru; Sakuma, Wakana; Lin, Jia-Rong; Tan-No, Koichi
Abstract: Adenosine monophosphate-activated protein kinase (AMPK) is critical for whole-body energy metabolism regulation. Recent studies have suggested that physical exercise ameliorates depressive-like behaviors via AMPK activation; however, the underlying mechanism is unclear. Here, we examined the effects and underlying mechanisms of AMPK activation on depressive-like behavior in olfactory bulbectomized (OBX) mice. We treated OBX mice with the AMPK activator, 5-aminoimidazole-4-carboxamide-1-β- d -ribonucleotide (AICAR) on the 7th or 14th day after bilateral bulbectomy and evaluated depressive-like behavior using the tail-suspension test (TST) and forced swimming test (FST) on the 21st day. The expression of phosphorylated AMPK, protein kinase C ζ (PKCζ), nuclear factor-kappa B (NF-κB), brain-derived neurotrophic factor (BDNF), and cAMP response element-binding protein (CREB) in the hippocampus was assessed by western blotting. Hippocampal neurogenesis and localization of AMPK and phosphorylated NF-κB were examined by immunohistochemistry. Chronic AICAR treatment suppressed the prolonged immobility of OBX mice in the TST and FST, and increased the levels of phosphorylated AMPK, PKCζ, NF-κB, CREB, and BDNF. Hippocampal neurogenesis in OBX mice was promoted by chronic AICAR treatment. Co-administration of AICAR with the PKCζ inhibitor or the neurotrophic tyrosine kinase receptor type 2 (TrkB) antagonist, ANA-12, inhibited these effects. Phosphorylated AMPK was detected in mature and immature hippocampal neurons and microglia, while phosphorylated NF-κB was detected only in neurons in AICAR-treated OBX mice. These data indicate that AMPK activation produces anti-depressant effects, which are mediated by elevated hippocampal neurogenesis potentially via PKCζ/NF-κB/BDNF/TrkB/CREB signaling in neurons. Graphical abstract: Image 1 Highlights: ・AMPK activator AICAR ameliorates depressive behavior in OBX mice. ・AICAR activates PKCζ/NF-κB/BDNF/TrkB/CREB pathway in the hippocampus of OBX mice. ・AICAR promotes neurogenesis, and this effect is attenuated by PKCζ inhibitor. ・Phospho-AMPK is detected in neurons and microglia; NF-κB is detected in neurons. ・AMPK activators may serve as new therapeutic targets in depression.